와이브로 활성화 정책 개선 방안 - 차성민(Seong-Min Cha) (한국비교정부학보, 2009)
WiBro(Wireless Broadband Internet), known as mobile WiMax overseas, is Korea's homegrown technology that lets people on the road remain hooked up to the Internet at the speed of today's fixed-line broadband. Is WiBro the future of broadband Internet services or the next famous high-tech industry bust? It is very difficult to answer the question. Current regulations of WiBro sector has not reflected the actual situation of market promptly. It causes so called 'delay of regulation' which prevents the growth of related industry. To facilitate the WiBro market, what should korean government do? In this paper, it is reviewed the preconditions for WiBro facilitation by specialists survey(FGI). The survey shows that the WiBro regulation is too strong generally, therefore Korean Communications Commission(KCC), the country's broadband and telecommunications regulator has to use some means to improve of WiBro industry. First, The regulator has to allow voice calls on WiBro networks and assigning call numbers to WiBro-enabled devices. Second, it must consider granting a license to a company to voice calls over WiBro as a mobile virtual network operator(MVNO), leasing the networks of KT and SK Telecom. Third, the cheaper price has to be maintained a considerable long time. Finally, it is necessary to make a support policy for WiBro company's overseas expansion. KCI Citation Count: 5